The Paradox of Character Education: Scouting as a Means of Covert Militarization in Indonesian Schools - Fikri, Mohammad (Faiyadhah | Journal of Islamic Education Management, 2025)
Scouting activities in Indonesian secondary schools are formally framed as instruments of character formation through discipline, responsibility, and obedience. Field observations, however, reveal that routines such as marching drills, uniform inspections, and behavioral standardization foster hidden militarization embedded within the hidden curriculum, shaping school culture and pedagogical relationships. Adopting a qualitative case study design, the research involved eight secondary schools in East Java, employing in-depth interviews, participatory observations, and policy document analysis, followed by Miles, Huberman, and Saldaña's interactive analytic model. Findings demonstrate that scouting successfully cultivates orderliness and procedural discipline yet simultaneously constructs a compliance habit that constrains dialogic spaces and suppresses student voice. These disciplinary norms permeate classroom practices, reinforcing hierarchical teacher-student relationships and exposing a paradox between the goals of character education and the Merdeka Belajar policy, which promotes creativity and participatory learning. Theoretically, the research enriches studies on the hidden curriculum by operationalizing soft militarization within Indonesian secondary education. Practically, it proposes strategies for dialogic discipline to balance procedural order with academic freedom, enabling scouting-based character education to foster learners who are not only compliant but also critical, creative, and actively engaged.